Pengembangan prototipe mesin pencacah rumput laut yang telah melalui proses alkalisasi (ATC) - M Marsono; S Septian (Jurnal Teknik Mesin Indonesia, 2018)
Carrageenan which is needs in food processing industry, either in Indonesia or in the world continues to increase due to the growth of the world population. One of the variants of carrageenan recognized world is SRC (Semi Refined Carrageenan) with standard E407A. SRC can be produced from ATC (Alkali Treated Cottonii). To produce SRC flour, dried ATC must be chopped first and then proceed with the grinding process. Field studies that have been done give a picture that the seaweed chopping machine that available on the market has not effective and efficient to chopp dry ATC. In this research, the prototype of ATC Chopping machine was developed with slicing mechanism through the pairs of rotating blade and fixed blade. From testing that has been perfomed, the results shows that slicer mechanism capable to chopp dry ATC with variation of length between 1cm to 3 cm and minimum production capacity of 180 kg/h.